Traumatic ventricular septal defect. Issue 3 (September 1997) - Genoni, M.; Jenni, R.; Turina, M.
Abstract : A 26 year old man was admitted to hospital following a traffic accident. He had been sitting in the back of a car without wearing a seat belt. He suffered crush injuries on the anterior chest wall, trunk, and legs. On admission he was awake and cooperative, but restless, and obviously in severe pain. Radiography of the skull, facial bones, chest, spine, pelvis, and legs revealed a shaft fracture of the left femur and tibia and fracture of the 7th and 8th right ribs. The patient was transferred to the University Hospital of Zurich for further assessment and surgical repair of the lower limb fractures three days later. Because of worsening clinical condition with onset of partial respiratory insufficiency and new loud systolic murmur at the left sternal edge, a transthoracic echocardiography was performed, which showed an apical ventricular septal defect. Surgery was performed immediately. The ventricular septal defect was successfully repaired using a Teflon felt patch and interrupted sutures with pledgets, and sealed with glue. At six months' follow up the patient was doing well. Ventricular septal defects after blunt chest trauma occur either because of heart compression between sternum and the spine or because of myocardial infarction. In the present case the ventricular septal defect appeared three days after the accident, probably secondary to a post-traumatic myocardial infarction. Patients with blunt chest trauma and suspicion of cardiac contusion should be monitored carefully.